Cable TV and communication segmentation - Andrelo, Roseane (2008)
The paper discusses the increasingly segmentation of cable tv channels, trying to show how the audiences position themselves in relation to that development. In order to do that a qualitative research was performed with two different publics: adults and children/teenagers.